RANCANG BANGUN SISTEM INFORMASI DOKUMEN KERJASAMA BERBASIS WEB (STUDI KASUS : STIKES BHAKTI HUSADA MULIA MADIUN) - Kusdwiadji, Agustinus; Budisaputro, Crismantoro (JURNAL PILAR TEKNOLOGI : Jurnal Ilmiah Ilmu Ilmu Teknik, 2021)
A database-based information system is a supporting application program for a university to make it easier to provide information services for users and accelerate the implementation of tasks or jobs effectively and efficiently. Cooperation is one of the main keys to success for a university; this is related to the existence of points in the accreditation assessment, namely the number of collaborations carried out by universities with related parties. The existence of an information system that manages documents and archives related to cooperation can make it easier for users to access and retrieve data for decision-making. This information system also provides access as needed to leaders, campus management, and stakeholders related to data and information managed by the Public Relations Section of Stikes Bhakti Husada Mulia Madiun. This research produces an information system that can be accessed easily by related parties who need the document in the form of archived data in a web-based application. Access to the application is required and is a basis for role permissions so that users who enter using this application can be controlled so that data security is more guaranteed.